Improving language use in early elementary science lessons by using a video feedback intervention for teachers. Issue 5 (18th August 2019) - van Dijk, Marijn; Menninga, Astrid; Steenbeek, Henderien; van Geert, Paul
ABSTRACT: We developed a teacher professionalisation intervention, called "Language as a Tool for Learning Science", that focuses on language use during early elementary science lessons, based on video feedback coaching. The aim of this study was to investigate possible changes in teacher student behaviour during this intervention, by analysing teacher-student language during science lessons. Seventeen teachers participated with small teaching groups of 4–6-year-old students. All task-related communication was coded for teacher questions, teacher language, student language, and reasoning skills. The results show that teachers in the intervention group increasingly used open-ended questions, and students used more utterances related to reasoning. The language of teachers in the intervention group also increased in complexity and sophistication. The students' language also increased in complexity, but also in the control group. These findings offer insights into effective forms of professional development for teachers in early elementary education.